A new flexible antenna for RFID applications / Nur Adyani Mohd Affendi - Mohd Affendi, Nur Adyani (Institute of Graduate Studies, UiTM, 2018)
Flexible substrates have drawn considerable interest in providing new opportunities for future applications of telecommunication antennas. This thesis is dedicated to the development and application for an indoor/outdoor wearable antenna such as tagging or identification system for Radio Frequency Identification (RFID) using natural rubber (NR) composites. The thesis is divided into two parts. The first half focuses on the preparation of NR composites to achieve a material with optimal mechanical and electrical properties. The formulation consists of carbon black as the main filler, and other supporting ingredients as activators, anti-oxidants, softeners and accelerators. The preparation process of these samples consisted of mastication, mixing, curing and moulding. To quantify the flexibility of these samples, tensile tests were conducted according to the ASTM D638 standard using an Instron machine. The second half of the thesis concerns antenna development. Meander dipole antennas with a combination of capacitive tip-loading and T-matching were designed using CST Microwave Studio. The substrates employed in the design had permittivity of 3.3 and loss tangent 0.008. The overall dimensions of the antenna are 65 × 65 × 1.0 mm³. The UHF band was chosen with the operating frequency of the proposed antenna selected at 921 MHz…